Prospects of pulp aeration for the cleaner production of pyrrhotite-rich type copper sulfide ore: Mechanism and application. (20th June 2023) - Wang, Changtao; Liu, Runqing; Zhai, Qilin; Dong, Wenchao; Xie, Zhenhui; Sun, Wei; Hu, Wenjihao
Abstract: Mineral extraction is facing increasingly severe challenges in terms of environment protection and cost reduction. Abundant of lime and sulfuric acid were consumed in the traditional high alkaline process (HAP) to extract chalcopyrite and iron sulfides. In this study, pulp aeration process (PAP) was proved a low-cost and environment friendly method in the processing of a pyrrhotite-rich type copper sulfide ore. Flotation results confirmed that pulp aeration was able to selectively depress pyrrhotite and pyrite flotation under ML8 system, thus 3000 g/t lime was cancelled during copper flotation stage, and around 4000 g/t sulfuric acid was saved during the subsequent sulfur flotation stage due to the low initial pulp pH. In the novel PAP, the directly production cost decreased by 4.34 RMB/t, besides, approximately 3.6 kg carbon dioxide and other waste could be reduced indirectly. Mechanism research revealed that pulp aeration oxidized the surface of pyrrhotite and pyrite, which further depressed the subsequent ML8 adsorption. However, the adsorption of ML8 on chalcopyrite was stable enough and it was unaffected by pulp aeration. Overall, pulp aeration was an environment friendly and cost-effective method for the separation of high-pyrrhotite type copper sulfide ore, which possessed broad industrial application prospects. Highlights: Lime and sulfuric acid were necessary in the traditional high alkaline process. Pulp aeration was able to replace lime to depress pyrrhotite and pyrite under ML8 system. Pyrrhotite was selectively oxidized by pulp aeration, thus ML8 adsorption was hindered. Pulp aeration process (PAP) was suitable to deal with pyrrhotite rich type copper sulfide ore. The PAP was of low cost and environmental friendliness and possessing broad application prospects.